Forage establishment and evaluation protocol, now being used by Seed Control and Certification Institute (SCCI) in Zambia - Muruu, David; Mwendia, Solomon; Hoppen, Sarah; Jauregui, Rosa (2025)
To guide in assessing the adaptation and performance of forage grass cultivars and accessions across six contrasting Zambian environments